An in vitro scratch tendon tissue injury model: effects of High Frequency Low Magnitude loading. - Adekanmbi, I; Zargar, N; Hulley, P; Zargar Baboldashti, N (Taylor and Francis, 2016)
The healing process of ruptured tendons is suboptimal, taking months to achieve tissue with inferior properties to healthy tendon. Mechanical loading has been shown to positively influence tendon healing. However, High frequency low magnitude (HFLM) loads which have shown promise in maintaining healthy tendon properties,have not been studied with in vitro injury models. Here we present and validate an in vitroscratch tendon tissue injury model to investigate effects of HFLM loading on the properties ofinjured rat tail tendon fascicles (RTTFs). A longitudinal tendon tear was simulated using a needle aseptically to scratch a defined length along individual RTTFs. Tissue viability, biomechanical and biochemical parameters were investigated before and 7days after culture. The effects of static, HFLM(20Hz), low frequency(1Hz) cyclic loading or no load were also investigated. Tendon viability was confirmed in damaged RTTFs after 7days of culture and the effects of a 0.77±0.06cm scratch on the mechanical property(tangent modulus) and tissue metabolism in damaged tendons were consistent, showing significant damage severity compared with intact tendons. Damaged tendon fascicles receiving HFLM(20Hz) loads displayed significantly higher mean tangent modulus than unloaded damaged tendons(212.7±14.94 v 92.7±15.59MPa), and damaged tendons receiving static loading(117.9±10.65MPa). HFLM stimulation maintained metabolic activity in 7day cultured damaged tendons at similar levels to fresh tendons immediately following damage. Only damaged tendons receiving HFLM loads showed significantly higher metabolism than unloaded damaged tendons(RFU-7021±635.9 v 3745.1±641.7). These validation data support the use of the custom in vitroinjury model for investigating the potential of HFLM loading interventions in treating damaged tendons.